0015 Effectiveness-Implementation Study of Two Novel Lighting Interventions for Shiftworkers on a Submarine Watchfloor. (25th May 2022) - Bessman, Sara; Harrison, Elizabeth; Easterling, Alexandra; Phares, Ashley; Teisberg, Madeline; Snider, Michelle; Robertson, Ian; Glickman, Gena
Abstract: Introduction: Shiftwork is common in the military, where around-the-clock readiness is necessary. Yet, non-standard schedules can negatively impact sleep, circadian health, and performance. Light is a leading countermeasure due to its phase shifting and alerting properties, with higher intensities and shorter wavelengths eliciting relatively greater effects. New technologies allow for deliberate spectral engineering that targets specific photobiological responses. This study examined the efficacy and implementation of two spectrally-distinct lights for improving sleep, alertness, and performance in active duty service members working nightshift schedules. Methods: Participants were service members working 12-h shifts (0530-1730) on a high-security, submarine watchfloor (N=56, 9 females; mean+SE age=28.95 + 0.76). Lighting interventions included LED panels (3, 721 cm2) that were either enhanced (SW+) or depleted (SW-) in short wavelength energy, while maintaining a comparable color temperature ( 3000 K) and photopic illumination ( 300 lux at 46 cm from eyes). For both SW+ and SW-, a bank of light panels were arranged across the front of the watchfloor and illuminated for the full duration of the nightshift. In addition, participants wore blueblocker glasses after nightshifts up until bedtime, when eye masks were worn during sleep. There were two data collection periods that coincided with existing 16-day schedule cycles: the first contained an 8-day baseline (BL1) and 8-day SW+ condition, and the second contained an 8-day baseline (BL2) and 8-day SW- condition (order within those 16-day periods was pseudo-randomized). Sleep and alertness were assessed via actigraphy, sleep diary, psychomotor vigilance test (PVT), and Karolinska Sleepiness Scale (KSS). Implementation metrics were obtained with questionnaires. Results: All analyses are still ongoing. Preliminary examinations show higher satisfaction with the SW+ than BL1, and greater comfort and fewer symptoms under both SW+ and SW- as compared to BL1. Most felt the SW+ and SW- improved alertness on shift and expressed an interest in keeping the lights on the watchfloor. Conclusion: Findings thus far indicate the interventions were well-received by participants. Subsequent analyses will further examine barriers to intervention use and the efficacy of the lights for improving sleep, alertness, and performance in service members working nightshifts. Support (If Any): ONR TS-788